Herd-level prevalence of selected endemic infectious diseases of dairy cows in Great Britain - Velasova, Martina; Damaso, Angela; Prakashbabu, Bhagyalakshmi Chengat; Gibbons, Jenny; Wheelhouse, Nick; Longbottom, David; Van Winden, Steven; Green, Martin; Guitian, Javier (American Dairy Science Association, 2017)
To implement appropriate and effective disease control programs at the national level, up-to-date and unbiased information on disease frequency is needed. The aim of this study was to estimate the prevalence of selected endemic infectious diseases in the population of dairy herds in Great Britain. Bulk milk tank (BMT) samples from 225 randomly selected dairy farms, stratified by region and herd size, were tested for antibodies against bovine viral diarrhea virus (BVDV), bovine herpesvirus type 1, Mycobacterium avium ssp. paratuberculosis, Leptospira Hardjo, Salmonella spp., Coxiella burnetii, Fasciola hepatica, Neospora caninum, and Ostertagia ostertagi. Furthermore, the presence of BVDV, C. burnetii, and Chlamydia-like organisms was determined by PCR. The apparent herd prevalence was estimated as a weighted proportion of positive herds. The true prevalence was calculated when a test was used with known test characteristics for the cut-off value used. Among unvaccinated herds, the true prevalence of BMT antibodies against BVDV was estimated at 66% [95% confidence interval (CI): 56–77%], M. avium ssp. paratuberculosis 68% (95% CI: 59–77%), bovine herpesvirus type 1 62% (95% CI: 52–73%), Leptospira Hardjo 47% (95% CI: 34–60%), and Salmonella spp. 48% (95% CI: 39–56%). The apparent prevalence of BMT antibodies against C. burnetii was 80% (95% CI: 75–85%), F. hepatica 55% (95% CI: 48–62%), N. caninum 46% (95% CI: 38–54%), and O. ostertagi 95% (95% CI: 91–98%). The BVDV, C. burnetii, and Chlamydia-like antigens were detected in 5 (95% CI: 2–9%), 29 (95% CI: 21–36%), and 31% (95% CI: 24–38%) of herds, respectively. Our results show that dairy cows across GB are frequently exposed to the studied pathogens, which are endemic at high levels with some geographical variations. These prevalence estimates provide a much-needed basis to assess whether nationwide control programs for the studied pathogens are justified by their potential economic, environmental, and public health implications. Should surveillance and control programs be initiated, the estimates presented here are a baseline against which progress can be assessed.